2020
DOI: 10.1016/j.ijcha.2020.100603
|View full text |Cite
|
Sign up to set email alerts
|

DIagnostic accuracy oF electrocardiogram for acute coronary OCClUsion resuLTing in myocardial infarction (DIFOCCULT Study)

Abstract: Background Although ST-segment elevation (STE) has been used synonymously with acute coronary occlusion (ACO), current STE criteria miss nearly one-third of ACO and result in a substantial amount of false catheterization laboratory activations. As many other electrocardiographic (ECG) findings can reliably indicate ACO, we sought whether a new ACO/non-ACO myocardial infarction (MI) paradigm would result in better identification of the patients who need acute reperfusion therapy. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 42 publications
1
41
0
1
Order By: Relevance
“…In contrast, our blinded interpreters were able to more than double the sensitivity of the STEMI criteria for OMI, with similar specificity. Our ability to reclassify NSTEMIs as STEMI(−) OMI externally confirms the results of Aslanger et al who also recently demonstrated the potential of the OMI paradigm [7] . Our interpreters exhibited very high interrater reliability among many ECGs, which is likely attributable to the fact that Interpreter 2 has been trained extensively by Interpreter 1.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, our blinded interpreters were able to more than double the sensitivity of the STEMI criteria for OMI, with similar specificity. Our ability to reclassify NSTEMIs as STEMI(−) OMI externally confirms the results of Aslanger et al who also recently demonstrated the potential of the OMI paradigm [7] . Our interpreters exhibited very high interrater reliability among many ECGs, which is likely attributable to the fact that Interpreter 2 has been trained extensively by Interpreter 1.…”
Section: Discussionsupporting
confidence: 88%
“…Investigators find many patients with OMI have STE that does not meet STEMI criteria, and have found many other ECG indicators of OMI, including hyperacute T-waves, terminal QRS distortion, low QRS amplitude, and more [6] . Aslanger et al recently reclassified 28% of NSTEMIs as OMI with structured interpretation using predefined OMI ECG findings, identifying a group with similar lesions and outcomes as STEMI [7] . Furthermore, some OMI have no ECG manifestations and must be diagnosed by a combination of clinical suspicion, ongoing symptoms, biomarker elevation, echocardiography, or even coronary computed tomography angiography [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if all such trials were free of these methodological issues and had instead shown no benefit, they still would not be applicable to the question of whether the subset of NSTEMIs with ACO benefit from emergent reperfusion because these trials did not report the presence or absence of angiographic ACO, much less the outcomes in these patients. These findings have 2 important messages with the same implication: We need to reshape our minds to understand that ACO needing reperfusion is clearly not synonymous with STEMI because NSTEMI with unrecognized ACO has higher short and long-term risk of mortality than NSTEMI with an open artery and similar to STEMI (39,40). In addition, although the current guidelines recommend urgent (<2 hours) invasive evaluation "regardless of ECG or biomarker findings" in patients with persistent pain, hemodynamic compromise, severe heart failure, and/or arrhythmias to identify patients with ACO but without STE (17)(18)(19), these clinical parameters did not compensate for the silence of the ECG in the abovementioned studies.…”
Section: Caveats Of the Stemi/nstemi Paradigmmentioning
confidence: 99%
“…The most widely recognizable and accepted ECG feature of OMI is ST-elevation (STE) meeting criteria specified in the Fourth Universal Definition of Myocardial Infarction (UDMI) [1]. However, not all OMIs manifest STE meeting these criteria, or even any STE at all [2,3]. Among the many OMIs not captured by the STE criteria are OMI associated with left bundle branch block (LBBB) and Right Ventricular Pacing (RVP).…”
Section: Introductionmentioning
confidence: 99%